Keanekaragaman Crustacea yang Didaratkan di Pangkalan Pendaratan Ikan (PPI) Ujong Baroh, Aceh Barat - Friyuanita Lubis; Revani Sri Handayani Sembiring; Mira Mauliza Rahmi; Azrina Sufi Nasution; Zahra Rodliyatam Mardliyah (Journal of Aceh Aquatic Sciences, 2025)
West Aceh waters, one of the coastal areas across front the Indian Ocean. Fishermen generally catch various types of crustaceans. This research aims to identify crustacean types and determine the value of diversity as a determinant of the status of West Aceh waters. This research was conducted using a survey method in June - July 2022. Initial sample identification was by sorting crustacean groups from fishermen's catches landed at PPI Ujong Baroh. Data were processed using the Shannon-Wienner diversity index. The results of this study indicate that the composition of fishermen's catches includes Acetes indicus (18%), Harpiosquilla raphidea (10%), Litopenaeu vannamei (15%), Metapenaeus ensis (14%), Metapenaeus monoceros (11%), Metapenaeus rosea (8%), Penaeus indicus (10%), Penaeus monodon (2%), Portunus sanguinolentus (12%). The diversity value (H') of crustaceans is classified as moderate (2.11). So, it can be assumed that West Aceh waters are vulnerable to pollution and disturbance.